Conhecimento dos profissionais de enfermagem sobre a prevenção da pneumonia associada à ventilação mecânica na unidade de terapia intensiva - Coelho, Viviane Ivani Martins (2012)
Ventilator-associated pneumonia (VAP) is an infection that most commonly affects critical patients admitted to the intensive care unit (ICU), resulting in significant morbidity and mortality rates. Objective: To assess nurses’ knowledge regarding the prevention of ventilator-associated pneumonia. Methods: A cross-sectional study was conducted on all nurses working at the ICU of the Polydoro Ernani de São ThiagoUniversity Hospital in Florianopolis between July 1st and August 30, 2012. A questionnaire was administered to 55 professionals, using a Likert scale (inadequate, satisfactory, good and excellent), which served as an evaluation parameter. Results: Nurses’ knowledge level regarding the prevention of ventilator-associated pneumonia was good (69.1%) or satisfactory (30.9%). Those who hold a college degree achieved better results (p = 0.04). No statistically significant association was found regarding working shift, postgraduate studies, gender, length of time working at the ICU, time elapsed since graduation, participation in training courses and age. Good results were observed on the following variables: hand antisepsis (58.2%), glove wearing (72.7%), semi-recumbent position (60.0%), aspiration of secretions (63.6%), ventilator circuits (52 7%), epidemiological surveillance (52.7%) and staff training (83.6%).Nurses’ knowledge regarding the aspiration system was considered good (56.4%). Fair results were observed on the following variables: oral hygiene (74.5%), humidifier filter (89.1%), nebulizer (65.5%), wall humidifier(45.5%) and non-invasive ventilation (47.3%). The poorest results were observed on these variables: enteral nutrition (94.5%), cuff pressure (63.6%) and tracheostomy (65.5%), whichwas considered unsatisfactory. The majority (60.0%) of the nurses reported that they had not received any guidance on VAP prevention. Conclusion: We concluded that the nurses’ knowledge was good or satisfactory on most aspects. Greater investment in educational programs should be made to promote behavior change and awareness of ICU staff towards VAP problems.